The Influence of Betawi Cultural and Social Factors on Food Choices Among Breastfeeding Mothers at the Cilincing Subdistrict Public Health Center, North Jakarta - Hutapea, Rismawati; Rambey, Harris; Nursaputri, Ika; Sirait, Reni Aprinawaty; Ginting, Desi Deria Yosepha (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background : Food choices among breastfeeding mothers are influenced by various factors, including the socio-cultural background of the surrounding community. Objective : This study aims to examine the socio-cultural factors of the Betawi ethnic group related to food selection among breastfeeding mothers in the working area of the Cilincing Subdistrict Public Health Center, North Jakarta. Research Methode : This research employed a mixed method design. The quantitative component used an observational analytic approach with a cross-sectional design, involving 66 breastfeeding mothers selected through purposive sampling. Data were collected using questionnaires and analyzed using chi-square and logistic regression tests. The qualitative data were obtained through in-depth interviews with three main informants and two key informants, then analyzed thematically and presented in narrative form. Result : The quantitative findings revealed significant associations between food choices and family support (p=0.002), knowledge (p=0.018), education (p=0.039), and socioeconomic status (p=0.001). Socioeconomic status emerged as the most dominant factor based on multivariate analysis (p<0.05). The qualitative findings identified several major themes: dietary restrictions imposed by family members, dependence on traditional information, belief in myths, and economic limitations affecting food and beverage choices during the breastfeeding period. It is recommended that future research further explore other local cultural factors influencing breastfeeding mothers' dietary behaviors and develop nutrition education strategies rooted in local wisdom.